2023
DOI: 10.5114/polp.2023.126111
|View full text |Cite
|
Sign up to set email alerts
|

The concentration of IL-6, TNF-α, s-ICAM-1, and EBV DNA load – predictive factors of hepatological complications in children with infectious mononucleosis. A pilot study

Abstract: Introduction:The aim of the study was to assess the relationship between the concentration of pro-inflammatory cytokines such as interleukin 6 (IL-6), tumour necrosis factor α (TNF-α), soluble intercellular adhesion molecule 1 (s-ICAM-1), and Epstein-Barr virus (EBV) DNA viraemia in children with infectious mononucleosis and hepatitis. Material and methods: The Epstein-Barr virus DNA load in the plasma of 36 immunocompetent patients aged 2.5-18 years with a symptomatic (sore throat, cervical lymph node enlarge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 27 publications
1
0
0
Order By: Relevance
“…In immunocompetent patients, an EBV DNA viral load assessment is not currently recommended for the routine diagnosis of EBV infection. A pilot in-house study enrolling 36 children with serologically and molecularly confirmed EBV infection, as well as the current study enrolling 68 children, showed a statistically significant correlation between EBV DNA viral load and CRP level, TNF-α concentration, leukocyte count, and monocyte count [30]. A group of 54 children with hepatological complications in the course of EBV infection were analysed in detail, in which correlations among ALT activity, GGTP activity, the duration of symptoms, selected elements of the protein-cell system, and EBV DNA viral load levels were analysed.…”
Section: Discussionsupporting
confidence: 64%
“…In immunocompetent patients, an EBV DNA viral load assessment is not currently recommended for the routine diagnosis of EBV infection. A pilot in-house study enrolling 36 children with serologically and molecularly confirmed EBV infection, as well as the current study enrolling 68 children, showed a statistically significant correlation between EBV DNA viral load and CRP level, TNF-α concentration, leukocyte count, and monocyte count [30]. A group of 54 children with hepatological complications in the course of EBV infection were analysed in detail, in which correlations among ALT activity, GGTP activity, the duration of symptoms, selected elements of the protein-cell system, and EBV DNA viral load levels were analysed.…”
Section: Discussionsupporting
confidence: 64%